Mechanism of Chemical Degradation and Determination of Solubility by Kinetic Modeling of the Highly Unstable Sesquiterpene Lactone Nobilin in Different Media. Issue 10 (29th August 2014) - Thormann, Ursula; De Mieri, Maria; Neuburger, Markus; Verjee, Sheela; Altmann, Peter; Hamburger, Matthias; Imanidis, Georgios
<x xml:space="preserve">Abstract</x> The objective of this work was first to investigate the chemical degradation of the sesquiterpene lactone nobilin and determine its solubility under conditions of concurrent degradation for partially amorphous starting material; second, to determine the effect of biorelevant media used in the in vitro measurement of intestinal absorption on degradation and solubility of nobilin. Purely aqueous medium (aq‐TMCaco), fasted and fed state simulated intestinal fluid (FaSSIF‐TMCaco and FeSSIF‐TMCaco), and two liposomal formulations (LiposomesFaSSIF and LiposomesFeSSIF) with the same lipid concentration as FaSSIF‐TMCaco and FeSSIF‐TMCaco were used. Degradation products were identified by nuclear magnetic resonance and X‐ray crystallography and the order of reaction kinetics was determined. Solubility was deduced with a mathematical model encompassing dissolution, degradation, and reprecipitation kinetics that took into account particle size distribution of the solid material. Degradation mechanism of nobilin involved water‐catalyzed opening of the lactone ring and transannular cyclization resulting in five degradation products. Degradation followed first‐order kinetics in aq‐TMCaco and FaSSIF‐TMCaco, and higher‐order kinetics in FeSSIF‐TMCaco and the two liposomal formulations, whereas degradation in the latter media was diminished. Solubility of nobilin increased in the order: aq‐TMCaco < FaSSIF‐TMCaco, < LiposomesFaSSIF < FeSSIF‐TMCaco < LiposomesFeSSIF. Improvement of stability and solubility was consistent with the incorporation of the nobilin molecule into colloidal lipid particles. The developed kinetic model is proposed to be a useful tool for deducing solubility under dynamic conditions. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3139–3152, 2014